Validation of the GenesWell BCT Score in Young Asian Women With HR+/HER2− Early Breast Cancer - Kwon, Mi Jeong; Ryu, Jai Min; Cho, Soo Youn; Nam, Seok Jin; Kim, Seok Won; Lee, Jeeyeon; Lee, Soo Jung; Park, Ji-Young; Park, Ho Yong; Hong, Sungjun; Kim, Kyunga; Han, Jinil; et al. (Frontiers in Oncology, 2021)
Background: The prognostic or predictive value of commonly used multigene assays in young patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2-) early breast cancer is unclear. In this study, we assessed the prognostic value of the GenesWell BCT assay according to age group. Methods: We identified patients with pN0-1, HR+/HER2- breast cancer in a prospective cohort of women who underwent surgery between 2005 and 2017. The GenesWell BCT assay was performed on tissue samples from selected patients. Distant metastasis-free survival (DMFS) and disease-free survival (DFS) were compared between the risk groups assigned by the BCT score. Results: A total of 712 patients were eligible for analysis. The median follow-up time was 7.47 years. The BCT score was prognostic in patients aged <=50 years (n = 404) and those aged >50 years (n = 308). In both age groups, the 10-year DMFS and DFS rates for patients classified as high risk by the BCT score were significantly lower than those for patients classified as low risk. A multivariate analysis revealed that the BCT score was an independent prognostic factor for DFS in patients aged <=50 years (hazard ratio, 1.28; 95% CI, 1.05–1.56; P = 0.015), as well as those aged >50 years. Conclusion: The BCT score could be used to identify low-risk patients who will not benefit from adjuvant chemotherapy to treat HR+/HER2- early breast cancer regardless of age. A further prospective study to assess the prognostic and predictive value of the BCT score is required.